EFEK SITOTOKSIK EKSTRAK ETANOLIK HERBA SELEDRI (Apium graveolens L.) PADA SEL KANKER T47D, WiDr, DAN HeLa - Palupi, Kartika Dyah; Wulandari, Ainun; Goenadi, Fina Aryani; Nur, Kholid Alfan; Fitriasari, Aditya; Meiyanto, Edy (University of Muhammadiyah Malang, 2011)
Celery (Apium graveolens L.) is commonly used to lower blood pressure, antirheumatic, relaxant, mild diuretic, antiseptic for the urinary tract, antioxidant, and anti-inflammation. According to previous studies, a number of the phytochemicals found in the plant show cytotoxicity toward some types of cancer cells. However, studies on the cytotoxic effects of celery herb ethanolic extract (CEE) on breast cancer cell (T47D), colon cancer cell (WiDr), and cervix cancer cell (HeLa), however, has not been done yet. Our research aims at doing so. Cytotoxicity test was conducted using MTT assay and its absorbance was read using ELISA reader at Î» = 595 nm. Results of the assay show that CEE reduces cell viability at concentrations of 100-750 Âµg/ml on HeLa cells, while reduction of T47D and WiDr cell viability was not achieved until concentrations of 500-750 Âµg/ml. Based on these results, we conclude that CEE hold many potentials for further developments as preventive and therapeutive agent in cancer treatment.